Answer:
Multiply by 8 through the entire equation to clear the fractions. Then solve the quadratic with the quadratic formula.
Step-by-step explanation:
To solve the equation, clear the fractions by multiplying the entire equation by 8.
8*[x/4 + 1/8 = x^2/ 4] becomes 2x + 1 = 2x^2
Now rearrange into standard form and use the quadratic formula to solve.
-2x^2 + 2x + 1 = 0 where a = -2, b = 2 and c = 1.
The quadratic formula is [tex]x=\frac{-b+/-\sqrt{b^2-4ac} }{2a}[/tex].
Substitute and you'll have:
[tex]x=\frac{-b+/-\sqrt{b^2-4ac} }{2a} =\frac{-2+/-\sqrt{-2^2-4(-2)(1)} }{2(-2)}=\frac{-2+/-\sqrt{4+8} }{-4)}[/tex]
[tex]\frac{-2+/-\sqrt{12} }{-4}=\frac{-2+/-2\sqrt{3} }{-4}=\frac{1+/-\sqrt{3}}{2}[/tex]